Utility of salivary mycophenolic acid concentration monitoring: Modeling and Monte Carlo validation approach - Aleksandra Catić‐Đorđević; Nikola Stefanović; Ivan Pavlović; Dragana Pavlović; Slavoljub Živanović; Ana Kundalić; Radmila Veličković‐Radovanović; Branka Mitić (Pharmacology Research & Perspectives, 2022)
Abstract The results of the previous studies demonstrated an association between mycophenolic acid (MPA) exposure, serum albumin level (ALB), and adverse effects in kidney transplant patients. The aim was the identification of mathematical correlation and association between both, total and unbound MPA concentration in relation to ALB, body mass (BM), age and estimated glomerular filtration rate (eGFR) in stable kidney transplant recipients. Furthermore, investigation was conducted with the aim to clarify the role of salivary concentration (CSAL) of MPA in adverse effect profile. In order to analyze the association between total and salivary concentration of MPA in relation to ALB, BM, age and eGFR, a least squares method for determining the correlation between these parameters was performed. In addition, derived mathematical model based on experimental data can also be performed and simulated through the Monte Carlo (MC) approach. Adverse effects were grouped according to the nature of symptoms and scored by a previously published validated system. Numerically calculated values of CSAL from the models [CSAL = f(ALB, BM, age, eGFR, CP) = a00 + a10*(ALB, BM, age, eGFR) + a01*CP] were then compared with those from validation set of patients, where the best fitting model was for ALB [CSAL = 54.96–1.64*ALB +13.4*CP]. Adverse effects estimation showed the difference in esthetic score, positively correlated with CSAL in the lower ALB group (145.41 ± 219.02 vs. 354.08 ± 262.19; with statistical significance p = .014) and almost significant for gastrointestinal score (167.69 ± 174.79 vs. 347.55 ± 320.95; p = .247). The study showed that CSAL MPA may contribute to management of adverse effects, but these findings require confirmation of clinical utility.